Investigation of Relationship between Bazaar and State in Iran under Hashemi Rafsanjani's Government (1368-1376) - vahid sinaee; sara akbari (رهیافتهای سیاسی و بین المللی)
The state and the bazaar have experienced variable relations as the two political and economic institutions in contemporary Iran, especially during the Islamic Republic. In the first decade , the state tried to decrease the bazaarc's influence and power in the political and economic spheres in the framework of centralized economic system. But with the arrival of the second decade and the beginning of the presidential term, Hashemi Rafsanjani, these relations have changed greatly. This change was influenced by the Taking the economic adjjustment policies by Rafsanjani in his first government, which provided the grounds for the empowerment and domination of the traditional right wing and the market in the major institutions and institutions of power and authority of the country. But gradually, since 1993, it created the grounds for a dispute between his state and the faction of the bazaar and led to confrontation between them. This article's main question is that how the economic policies influence the interaction between government and bazaar in the Hashemi Rafsanjani's first and second state. The authors' hypothesis is that although in the Hashemi' state first, with the implementation of liberalism policies, commercial and traditional capitalism in the context of the government was able to secure its own interests. But the new economic policies of the second state, the formation of the industrial capitalist class, the entry of foreign investment into the country, inflation, the change in the distribution system, and the creation of chain stores caused a dramatic change in the relations between the state and the bazaar.